Comparing Organic and Conventional Farming Systems: Metrics and Research Approaches. Issue 1 (29th April 2013) - Reganold, John P.
Abstract : With the rise of organic farming worldwide, researchers are being presented with new opportunities to study organic systems and also to compare them to their conventional counterparts. This paper focuses on farming systems research comparing organic and conventional agroecosystems. The types of farming systems comparison studies, some of the metrics used, and integrative research approaches to farming systems studies are discussed. To hasten implementation of more sustainable agricultural systems, more farming systems comparison research, especially interdisciplinary and transdisciplinary, is needed, which brings together multiple disciplines and, when possible, non‐academic participants to measure key sustainability indicators and/or ecosystem services. Such research does not just need to compare organic and conventional systems. In addition to organic farming systems, other innovative systems make up a modest, but growing, component of US and global agriculture and include alternative livestock production (e.g., grass‐fed), mixed crop/livestock systems, conservation agriculture, integrated farming, agroforestry, and perennial grains. Such systems integrate production, environmental, and socioeconomic objectives and reflect greater awareness of ecosystem services. These systems can be studied in farming systems research, in which they are compared with each other or with conventional systems.